1995
DOI: 10.1016/0304-3959(94)00164-a
|View full text |Cite
|
Sign up to set email alerts
|

Home management of sickle cell-related pain in children and adolescents: natural history and impact on school attendance

Abstract: Some children and adolescents with sickle cell disease experience frequent painful episodes. To gain information about the natural history of the pain and its impact on sleep and school attendance, we developed a home-based diary system. Eighteen children and adolescents completed 4756 diary days, with an average compliance of 75%. Pain was reported on 30% of days and was managed at home nine-tenths of the time. Girls reported more days with pain than did boys, and age was positively correlated with the length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
135
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(142 citation statements)
references
References 2 publications
6
135
1
Order By: Relevance
“…Pain is the complication that has the greatest impact on HRQL of patients with SCD and their families, although its intensity is variable and depends on individual characteristics, family and cultural context and the multiprofessional team that is responsible for their health care (6,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Pain is the complication that has the greatest impact on HRQL of patients with SCD and their families, although its intensity is variable and depends on individual characteristics, family and cultural context and the multiprofessional team that is responsible for their health care (6,16) .…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Aside from the direct physical morbidity of these recurrent painful attacks, other significant outcomes such as quality of life, school attendance, and societal participation of patients are greatly affected. [12][13][14][15][16][17][18] Moreover, high societal costs are involved. Direct costs arise from high health care utilization, and indirect costs include absence from work associated with impaired physical ability to perform daily tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Some absences were attributed to fear of accidents at school or even fabricated by the student to avoid attendance. The literature suggests that children with chronic illness miss more school than do their peers without illnesses (Caldwell et al, 1997;Sato et al, 2007;Shapiro et al, 1995;Wodrich & Cunningham, 2008). During initial interviews, Emily and her mother reported that Emily might miss anywhere from 1-3 days of school each week if she was not feeling well.…”
Section: Thematic Resultsmentioning
confidence: 99%
“…The lack of a viable educational support plan and specific plans for frequent home-school communication resulted in what everyone agreed to be academic underachievement for Emily. There is much support in the literature (both professional guidelines and research) for formal supports at school (American School Health Association, 2002;Best, 2005;Clay, 2004;Filce & LaVergne, 2011;National Association of School Nurses, 2013;Shapiro et al, 1995) as these children are at risk for underachievement (Best, 2005;Clay, 2004;Wodrich & Cunningham, 2008). The lack of awareness of Emily's 504 Plan, the low level of individualization in this plan, the ambiguity of processes and responsibilities, and an overall absence of regular communication all contributed to Emily's lackluster performance at school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation